2019
DOI: 10.1111/ppl.12928
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of CAC antenna proteins and photosystem I supercomplex from the cryptophytic alga Rhodomonas salina

Abstract: In the present paper, we report an improved method combining sucrose density gradient with ion‐exchange chromatography for the isolation of pure chlorophyll a/c antenna proteins from the model cryptophytic alga Rhodomonas salina. Antennas were used for in vitro quenching experiments in the absence of xanthophylls, showing that protein aggregation is a plausible mechanism behind non‐photochemical quenching in R. salina. From sucrose gradient, it was also possible to purify a functional photosystem I supercomple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The pigment-protein complexes of PSI and PSII of cryptophytes are localized in thylakoid membranes as monomers for PSI and as dimers for PSII, respectively, similar to those seen in other algae and higher plants 30 , 31 . The structure of PSI-light-harvesting antenna (LHCI) supercomplex from a cryptophyte alga Chroomonas placoidea ( C. placoidea ) has been determined by cryo-electron microscopy recently and reveals detailed composition and structural features of the PSI-LHCI complex 32 .…”
Section: Introductionsupporting
confidence: 57%
“…The pigment-protein complexes of PSI and PSII of cryptophytes are localized in thylakoid membranes as monomers for PSI and as dimers for PSII, respectively, similar to those seen in other algae and higher plants 30 , 31 . The structure of PSI-light-harvesting antenna (LHCI) supercomplex from a cryptophyte alga Chroomonas placoidea ( C. placoidea ) has been determined by cryo-electron microscopy recently and reveals detailed composition and structural features of the PSI-LHCI complex 32 .…”
Section: Introductionsupporting
confidence: 57%
“…For example, TPG clade species including strains of Teleaulax genus with particularly high eicosapentaenoic acid (EPA) contents are expected to be excellent food for the enrichment of prey zooplankton (Peltomaa et al 2018). RHO clade species are also known to have photophysically very efficient lightharvesting plastid systems (Doust et al 2006, Marin et al 2011, Kim et al 2015 with the key proteins such as phycobiliproteins, chlorophyll a/c antenna proteins, and photosystem I supercomplex in Rhodomonas salina (Kuthanová Trsková et al 2019).…”
Section: Experimental Strainsmentioning
confidence: 99%
“…The results indicated that the activity of this enzyme was governed by Fe supply to plants. Leaf proteins play a critical role in supporting and protecting photosynthetic pigments and preserving the integrity of the chloroplasts [ 71 , 72 ]. The majority of leaf proteins accumulate in the chloroplasts in association with chlorophylls [ 3 ].…”
Section: Discussionmentioning
confidence: 99%